2016
DOI: 10.1111/cxo.12383
|View full text |Cite
|
Sign up to set email alerts
|

Visual function in autism spectrum disorders: a critical review

Abstract: Studies have shown considerable evidence of visual dysfunction in autism spectrum disorders. Anomalies in visual information processing can have a major effect on the life quality of individuals with autism spectrum disorders. We summarise the hypotheses and theories underlying neural aetiologies and genetic factors that cause these disorders, as well as the possible influences of unusual sensory processing on the communications and behaviour characterised by the autistics. In particular, we review the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 138 publications
(250 reference statements)
2
38
0
Order By: Relevance
“…Another question that arises is whether these structural differences between ASD individuals and NT controls may be related to the atypical visual function in autism. 33 On the one hand, ASD subjects exhibited superior performance during static visual tasks, [34][35][36] but ASD individuals showed inferior performance during dynamic visual tasks. 37 It has also been demonstrated recently that the visual field was narrower in ASD patients than in NT controls 38 and that ASD subjects presented atypical electroretinograms.…”
Section: Discussionmentioning
confidence: 99%
“…Another question that arises is whether these structural differences between ASD individuals and NT controls may be related to the atypical visual function in autism. 33 On the one hand, ASD subjects exhibited superior performance during static visual tasks, [34][35][36] but ASD individuals showed inferior performance during dynamic visual tasks. 37 It has also been demonstrated recently that the visual field was narrower in ASD patients than in NT controls 38 and that ASD subjects presented atypical electroretinograms.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the complex inheritance pattern and possible genetic mutations can combine with environmental factors to yield varying expressions of ASD . For further reading on this and the neurobiological profile of ASD, see the recent review of Bakroon and Lakshminarayanan …”
Section: Aetiologymentioning
confidence: 99%
“…Simmons et al provided a comprehensive review of visual function in ASD with respect to the theories associated with ASD. More recently, Little and Bakroon have critically reviewed visual development and function in children with ASD. Recent systematic reviews have found there was a greater risk for children with ASD if they had a congenital hearing or visual impairment .…”
mentioning
confidence: 99%